Sik Bilong Ples: an Exploration of Meanings of Illness and Well-Being Amongst the Wosera Abelam of Papua New Guinea - Koczberski, Gina; Curry, George (1999)
This paper examines indigenous concepts of health and well-being amongst the Wosera Abelam, East Sepik Province, Papua New Guinea. Indigenous conceptual frameworks for understanding human well-being are remarkably resilient despite the use of western medical services and nutritional advice from health clinics. Their resilience is probably attributable to their embeddedness within a wider worldview that emphasises the social context of health and well-being and thus makes them resistant to change. Whilst the Wosera Abelam are open and receptive to modern health services, their response to these services remains considerably influenced by indigenous concepts of health and illness.